DEVELOPMENT OF TOLL FOR ROAD NETWORKS USING IN SOME OF EUROPES STATES AND SLOVAK REPUBLIC (Perner's Contacts, 2009)
Electronics tolls cost are important hauliers cost. This article analyzes to development of toll for road networks using in some of Europes states: Germany, Czech Republic, Austria, Poland,Hungary, Belgium, Netherlands, Luxemburg, Sweden, Denmark and Switzerland. The article analyzes to development and volume of tolling in Slovak Republic.
Keywords: road; transport; toll; cost; development